Occurrence of Salmonella and Vibrio species in fresh fishes collected from different markets of Mymensingh, Gazipur and Sherpur districts of Bangladesh and their characterization (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
This study was undertaken to determine total viable count (TVC), total salmonella count (TSC) and total vibrio count (TVibC) in fresh fishes collected from markets of Mymensingh, Gazipur and Sherpur districts. Isolation and identification of Salmonella spp. and Vibrio spp. was also done from pangas (n=20), tilapia (n=20) and koi (n=20) collected from different markets of Mymensingh, Gazipur and Sherpur districts. Samples were cultured on plate count agar to determine TVC, xylose-lysine deoxycholate agar (XLD) to determine TSC and thiosulfate citrate bile salt sucrose agar (TCBS) to determine TVibC. The mean value of logarithm colony forming units (CFU±SD/g) of TVC, TSC and TVibC in pangas were log 9.09±0.616, log 5.32±0.391 & log 3.14±0.557CFU/g; log 8.46±0.441, log 5.26±0.589 & log 3.59±0.823 CFU/g and log 7.58±0.466, log 3.28±0.493 & log 2.88±0.386 CFU/g of Mymensingh, Gazipur and Sherpur, respectively. Similarly, the mean values of TVC, TSC and TVibC in tilapia were log 6.60±0.790, log 3.59±0.388 & log 3.75±0.176 CFU/g; log 6.55±0.553, log 3.26±0.502 & log 3.67±0.021 CFU/g and log 6.74±0.372, log 3.44±0.411 & log 3.05±0.609 CFU/g of Mymensingh, Gazipur and Sherpur, respectively and in koi were log 7.51±0.537, log 3.49±0.459 & log 3.35±0.390 CFU/g; log 7.66±0.752, log 3.25±0.465 & log 3.59±0.581 CFU/g and log 7.13±0.393, log 3.27±0.384 & log 3.43±0.297 CFU/g of Mymensingh, Gazipur and Sherpur respectively. The targeted Vibrio spp. and Salmonella spp. were isolated and identified from collected fishes. All the isolates of Salmonella were confirmed by targeting genus specific histidine transport operon gene. Antimicrobial sensitivity test was done for all the isolates of Salmonella and Vibrio species by disc diffusion method. Out of forty five isolates of Salmonella, seven were found multidrug resistant. The bacteria isolated from fish were of public health significance as well as responsible for spoilage of fish.Asian Australas. J. Biosci. Biotechnol. 2018, 3 (1), 45-51